EKSTRAK BIJI ALPUKAT SEBAGAI PEMBUSA DETERJEN: “PEMANFAATAN POTENSI BAHAN ALAM DAN MENEKAN BIAYA PRODUKSI” - Hazena Misgi Damayanti; Nabila Annisa Praditia; Reni Widaya Murti; Midar Ahmad; Naniek Widyaningrum (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT The use of powder detergent in Indonesia started to increase dramatically in the 1990s. Raw materials for use in the formulation detergents are active ingredients, excipients, support materials, additives, fragrance materials, and antifoam. The active ingredients of detergents, such as Sodium Lauryl Sulfonate (SLS) are utilized to increase the cleaning power. SLS known as an import detergent active ingredients and has a high price. Avocado seed is known containing several secondary metabolites such as alkaloids, triterpenoids, tannins, flavonoids, and saponins. Saponins have an important role as a producer of foam in industrial detergents, soaps, and shampoos. The purpose of this study is to determine the effectiveness of the avocado seed extract as an additive in detergents production. This research was carried out by mixing the avocado seed extract concentration of 14%; 28%; 42%; 56% and 70% with other detergent ingredients. The measurements include the analysis of physicochemical properties as require: pH level, viscosity and foam stability. Data were analyzed theoretically and statistically by One-way ANOVA. The results show that the detergent formula avocado seed extracts 28% can be used as a substitute for SLS 28%. Key words: Seed Avocado, detergents, saponin, SLS